(untitled) (Nóema, 2012)
At the present time it is possible to observe a return to «values»: just for example, against the economic crisis or the dehumanization of care, hearing calls to the value of the person or to the person as a value is becoming more frequent. The requirements of the philosophical historiography, as stated by Pareyson, can give the opportunity to confirm these concepts.